La desnutrición crónica y su efecto generacional sobre el crecimiento: aporte de los estudios de antropología biológica experimental - Cesani Rossi, María Florencia (2017)
The prevalent form of malnutrition in human populations is characterized by its chronic and generational nature. Many people around the world live in deficient environments, with scarce economic resources and poor sanitation; further, the diets of children are deficient and unbalanced throughout life. Considering the multiplicity of factors that define these environments characterized by poverty and marginalization, malnutrition solely would not affect physical growth. In this sense, experimental studies allow us to isolate the aspect to be investigated (nutritional) and to use experimental animals (such as the rat), thus facilitating the study of many generations in a short time, which is impossible when human populations are considered. We performed a review of studies addressing this issue, particularly those in which the experimental method was used. We focused especially in the work developed by the research group led by Héctor Pucciarelli at the National University of La Plata.